Harvey - Koster, Henry, 1905-1988; Beck, John, 1909-1993; Brodney, Oscar; Stewart, James, 1908-1997.; Hull, Josephine, 1877-1957; Chase, Mary, 1907-1981. (Universal City, Calif. : Universal, 2000)
Comedy about a good-natured fellow whose constant companion is a six-foot tall invisible rabbit. His sister is determined to marry her daughter off and decides to commit her brother to a mental hospital to get him out of the way. Due to a mix-up the sister is committed instead, and it is up to the kindly brother and his imaginary friend to straighten things out!
Dolby digital, mono. ; full frame 1.33.1 aspect ratio.
Bonus material: special introduction by Jimmy Stewart, with photographic montage ; theatrical trailer ; production notes ; cast & filmmakers biographies and highlights.
Based upon the play by Mary Chase.
Universal International ; screenplay by Mary Chase, Oscar Brodney ; produced by John Beck ; directed by Henry Koster ; director of photography, William Daniels ; editor, Ralph Dawson ; music, Frank Skinner.
Jimmy Stewart, Josephine Hull, Charles Drake, Cecil Kellaway, Jesse White, Victoria Horne, Wallace Ford, Peggy Dow.
Originally produced as motion picture in 1950.
Keywords: Imaginary companions -- Drama; Involuntary treatment -- Drama; Brothers and sisters -- Drama; Films comiques; Video recordings; Feature films; Comedy films